(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2016)
The authors examine in this work the concept of line of research in the context of music in general, and in particular, of musicology as a discipline, from their own experience as researchers. Without entering into epistemological disquisitions, they recount how a line of research was born and grew out of a primary idea: to make original Venezuelan music for four-handed piano. From this starting point, it grew, developed and transformed organically, generating a series of processes and products in which other disciplines necessarily interact, gradually defining the line of research as something objective and concrete to which to refer.